2003
DOI: 10.1182/blood-2002-06-1736
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation-dependent inhibition of cutaneous lymphocyte–associated antigen expression: implications in modulating lymphocyte migration to skin

Abstract: Constitutive E-selectin expression on dermal microvascular endothelial cells plays a critical role in mediating rolling adhesive interactions of human skin-homing T cells and in pathologic accumulation of lymphocytes in skin. The major E-selectin ligand on human skin-homing T cells is cutaneous lymphocyte-associated antigen (CLA), a specialized glycoform of P-selectin glycoprotein ligand-1 (PSGL-1) defined by monoclonal antibody HECA-452. Since HECA-452 reactivity, and not PSGL-1 polypeptide itself, confers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 52 publications
8
94
0
Order By: Relevance
“…To analyze whether CD43 and CD44 also function as E-selectin ligands on NK cells, we pretreated DX5 ϩ CD90 Ϫ NK cells with a robust protease, bromelain, before lysate preparation. With the exception of ESL-1, an E-selectin ligand characteristically localized in the Golgi (34), bromelain digestion cleaves all cell surface E-selectin glycoprotein ligands on leukocytes (20,33,37). By flow cytometry, we first confirmed that bromelain treatment eliminated PSGL-1, CD43 and CD44 expression (data not shown).…”
Section: Glycolipid E-selectin Ligands Are a Major Component On Nk Cellsmentioning
confidence: 66%
See 4 more Smart Citations
“…To analyze whether CD43 and CD44 also function as E-selectin ligands on NK cells, we pretreated DX5 ϩ CD90 Ϫ NK cells with a robust protease, bromelain, before lysate preparation. With the exception of ESL-1, an E-selectin ligand characteristically localized in the Golgi (34), bromelain digestion cleaves all cell surface E-selectin glycoprotein ligands on leukocytes (20,33,37). By flow cytometry, we first confirmed that bromelain treatment eliminated PSGL-1, CD43 and CD44 expression (data not shown).…”
Section: Glycolipid E-selectin Ligands Are a Major Component On Nk Cellsmentioning
confidence: 66%
“…PBMC were first obtained from citrated-whole blood by density-gradient centrifugation as previously described (20). To prepare CD56 ϩ CD3 Ϫ NK cells, CD3 ϩ T cells were first depleted from PBMC using CD3 immunomagnetic beads (Miltenyi Biotec) and then CD56 ϩ cells were selected from CD3 Ϫ cells using CD56 immunomagnetic beads (Miltenyi Biotec).…”
Section: Cellsmentioning
confidence: 99%
See 3 more Smart Citations